Conceptual History and Literary Studies (Castilla. Estudios de Literatura, 2013)
In the field of the History of Political Thought, the Conceptual History, aided by Philology, has proved to be an useful tool to correct the anachronisms derived from the History of Ideas. Reinhard Koselleck from the field of German Theory, and Quentin Skinner and John Pocock from the Cambridge School have developed, from differents points of view, an accurate methodology to investigate historicial concepts and discourses. This article revises critically their basic characteristics, their differences and similarities. It wonders, finally, about its application in literary investigation and suggest some specific guidelines to make them effective.